Robust Interface Ru Centers for High‐Performance Acidic Oxygen Evolution. Issue 25 (17th May 2020) - Cui, Xiaoju; Ren, Pengju; Ma, Chao; Zhao, Jia; Chen, Ruixue; Chen, Shiming; Rajan, N. Pethan; Li, Haobo; Yu, Liang; Tian, Zhongqun; Deng, Dehui
Abstract: RuO2 is considered as the state‐of‐the‐art electrocatalyst for the oxygen evolution reaction (OER) in acidic media. However, its practical application is largely hindered by both the high reaction overpotential and severe electrochemical corrosion of the active centers. To overcome these limitations, innovative design strategies are necessary, which remains a great challenge. Herein, robust interface Ru centers between RuO2 and graphene, via a controllable oxidation of graphene encapsulating Ru nanoparticles, are presented to efficiently enhance both the activity and stability of the acidic OER. Through precisely controlling the reaction interface, a much lower OER overpotential of only 227 mV at 10 mA cm −2 in acidic electrolyte, compared with that of 290 mV for commercial RuO2, but a significantly higher durability than the commercial RuO2, are achieved. Density functional theory (DFT) calculations reveal that the interface Ru centers between the RuO2 and the graphene can break the classic scaling relationships between the free energies of HOO* and HO* to reduce the limiting potential, rendering an enhancement in the intrinsic OER activity and the resistance to over‐oxidation and corrosion for RuO2 . Abstract : The robust interface Ru centers between RuO2 and graphene are found to boost both activity and stability for the acidic oxygen evolution reaction (OER), exhibiting a much lower OER overpotential of only 227 mV at 10 mA cm −2 compared with that of 290 mV for commercial RuO2 but a significantly higher durability than the commercial RuO2 .